2013
DOI: 10.4025/actascibiolsci.v35i2.13408
|View full text |Cite
|
Sign up to set email alerts
|

Population parameters of the shrimp Xiphopenaeus kroyeri (Heller, 1862) (Crustacea, Penaeidae), caught by artisanal fisheries in Anchieta, Espírito Santo State

Abstract: The fishery on Penaeidae shrimp is done all over the Brazilian coast, especially the seabob shrimp (Xiphopenaeus kroyeri). It is captured in large quantities in the Southeast and Southern Brazil. In order to study the population structure of X. kroyeri from Anchieta Municipality, Espírito Santo State, during the period from January to December 2008, monthly samplings with one-hour-long were conducted to verify the number of individuals, biomass, sex, total length and gonad maturity stage. The specimens had tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…The overall sex ratio of the seabob shrimp X. kroyeri found in this study did not differ from (1:1). Similar results were observed in other Brazilian localities: in the studies by Branco (2005) in the State of Santa Catarina; Fernandes et al (2011) in the State of Rio de Janeiro; Eutrópio et al (2013) in the State of Espírito Santo; Heckler et al (2013a) and Castilho et al (2015) in the State of São Paulo. This pattern agreed with the theory of sexual allocation described by Fisher (1930), who assumed that for gonochoric species, the expected sex ratio is 1:1.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The overall sex ratio of the seabob shrimp X. kroyeri found in this study did not differ from (1:1). Similar results were observed in other Brazilian localities: in the studies by Branco (2005) in the State of Santa Catarina; Fernandes et al (2011) in the State of Rio de Janeiro; Eutrópio et al (2013) in the State of Espírito Santo; Heckler et al (2013a) and Castilho et al (2015) in the State of São Paulo. This pattern agreed with the theory of sexual allocation described by Fisher (1930), who assumed that for gonochoric species, the expected sex ratio is 1:1.…”
Section: Discussionsupporting
confidence: 84%
“…The shrimps from the Penaeidae Rafinesque, 1815 family are one of the main fishery resources in tropical coastal regions (Albertoni et al , 2003; Costa et al , 2007; Eutrópio et al ., 2013). Among these species, Xiphopenaeus kroyeri (Heller, 1862), popularly known as the seabob shrimp, is highlighted as the major fishery resource in Brazil (Albertoni et al , 2003; Costa et al , 2007; Campos et al , 2011; Eutrópio et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Dendrobranchiata, results of several studies have revealed a predominance of females in higher size classes, e.g., for Artemesia longinaris Bate (Castilho et al 2007a, Costa et al 2010), Pleoticus muelleri (Bate) (Castilho et al 2008a, Dumont and D’Incao 2008) and Sicyonia dorsalis Kingsley (Castilho et al 2008b), as well as for Xiphopenaeus kroyeri (Branco 2005, Castro et al 2005, Almeida et al 2012, Eutrópio et al 2013, Heckler et al 2013). These studies also collected overall more females than males, which concords with results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The shrimps of the family Penaeidae Rafinesque, 1815 are considered one of the most exploited fishing resources in coastal regions over the world (ALBERTONI et al, 2003;COSTA et al 2007;EUTRÓPIO et al, 2013). At the Brazilian coast, five species distributed in three genera represent the shrimps with greatest economic importance, the seabob shrimp Xiphopenaeus kroyeri (Heller, 1862), the white shrimp Litopenaeus schmitti (Bukenroad, 1936), and the pink shrimp Farfantepenaeus subtilis (Pérez-Farfante, 1967), F. brasiliensis (Latreille, 1817) and F. paulensis (Pérez-Farfante, 1967).…”
Section: Introductionmentioning
confidence: 99%